A cladistic analysis of the genera of the tribe Entimini (Coleoptera, Curculionidae), with description of a new genus and species from the Amazonian Region - Vanin, Sergio Antonio; Gaiger, Fabio (Zootaxa, 2005)
A new genus and species of the weevil tribe Entimini, Nasocomptus obyberaba gen. nov. and sp. nov., are described from the southwestern Amazonian Region (type locality: Brazil, Rondonia, Ouro Preto do Oeste). A cladistic analysis was carried out among representative species of most of the Neotropical genera, including Nasocomptus gen. nov., to provide a phylogenetic hypothesis for the tribe. A single most parsimonious cladogram was obtained: (Entimus (Nasocomptus ((Polyteles, Phaedropus) (Rhigus, Cydianerus)))). An identification key for the genera of Neotropical Entimini (except Trachyus) is furnished. The new genus is easily distinguished by two outstanding autapomorphies: anterior angle of rostrum prominent and spiked in males, and styli of female coxites ventral and pre-apical. Color photographs of the habitus of the new species and outline illustrations of structures used in the cladistic analysis are presented.